Komposisi dan Frekuensi Kemunculan Jenis Ikan Hasil Tangkapan Bagan Tancap di Tengkolak, Desa Sukakerta, Kabupaten Karawang, Jawa Barat - Dian Sutono Hs; Dendi Haris; Robet Perangin-angin; Untung Prasetyono; Maman Hermawan (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2021)
One of the capture fisheries activities in Tengkolak, Sukakerta Village, West Cilamaya District, Karawang Regency, West Java Province is using the stationery lift nett. The operation of the stationery lift nett itself cannot be separated from fishing aids that use light to attract the fish that are phototaxis positive. The purpose of this study was to determine the composition of the catch and to determine the number of catches based on the stationery lift nett in the waters of Karawang Regency. The benefits of this research can provide benefits to the lift net fishermen in the waters of Karawang Regency and become a reference for policy makers in the local area. Research data collection was carried out on a stationery lift nett operating in the waters of Karawang Regency, West Java. The implementation of the research stationery lift nett in March – May 2021. Sampling was carried out randomly every day based on ships that carried out fishing operations for 38 days, by collecting data on catches directly in the field, both the same and different fishing gear. It was obtained during the research that the fish caught in the stationery lift nett consisted of 9 fish speciess, consisting of anchovies, squid, acetes, sea-pike, dorab wolf, ninis, pony fishes, semadar and yellow-strips trevally. The catch was dominated by rebon (9,650 kg/45.34 %), while the highest frequency of occurrence was anchovy (100%).